ON THE QUESTION OF STABLE EXPRESSION TRANSLATION (IN KOREAN LANGUAGE) - Дилноза Насуллаева (Journal Park Publishing, 2023)
The article reveals the concept of stable expressions in the Korean language. Definitions of phraseological units in the Korean language are given. It is concluded that the phraseological unit has its own specifics and requires special attention.
Keywords: Phraseologies, stable expressions, linguistic forms, translation, culture, examples.